Perbedaan Pengetahuan dan Kesadaran Multikultural Mahasiswa Calon Konselor dua LPTK Indonesia - Irene Maya Simon; Rian Rokhmad Hidayat (Universitas Sebelas Maret, 2022)
This study aims to determine the profile of knowledge and multicultural awareness of prospective counselor students from two different LPTKs in Indonesia. This study uses survey and comparative research methods. The research data uses an adapted Multicultural Counseling Knowledge and Awareness Scale-Refined (MCKAS-R) questionnaire, which has been retested for validity and reliability using Indonesian students as subjects. The results showed that the students' multicultural competence level was in moderate condition. There is no difference in the level of multicultural competence between students in the two LPTKs. Viewed from the aspect of knowledge and multicultural awareness, students in both LPTKs are also in moderate condition. Efforts that can be made to improve students' multicultural competence start with self-awareness, knowledge, and multicultural skills so that students can later internalize these multicultural competencies.